Hear my heart [large type] : what I would say to you - Graham, Billy, 1918-2018 (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"America's pastor has gone home. But his lifelong message, his passion for the gospel, and his compassion for people still echo in Hear My Heart. This intimate work, a compilation of articles that spans Billy's ministry from 1955 to 2014, invites you to sit down with Billy and hear in his own unvarnished words the things that moved his heart regarding relevant issues of the day. The Biblical convictions he abided by. The reasons and regrets behind some of his decisions. And the wisdom he gained in his century on this earth. Hear My Heart also presents stirring tributes, collected over many years, about Billy and his legacy from those who knew him best in all the seasons of his life--including his family members, his friends, and his co-laborers in ministry. Though their lives may have changed, Billy's impact remains the same, and their words are beautifully preserved in essays that reflect the power of his ministry. This book was assembled and printed to be released upon his passing so that his final words would bring comfort and peace to the many lives he touched."--Amazon.com.